2015
DOI: 10.1111/eci.12442
|View full text |Cite
|
Sign up to set email alerts
|

Soluble triggering receptor expressed on myeloid cells‐1 is a biomarker of anti‐CCP‐positive, early rheumatoid arthritis

Abstract: Our results suggest that serum sTREM-1 may provide a novel biomarker for DMARD-naïve ERA as well as for seropositivity for anti-CCP antibody and RA activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 42 publications
0
26
4
Order By: Relevance
“…11 Different studies have observed an increase in plasma sTREM-1 levels in RA. [7][8][9] Choi et al observed that sTREM-1 levels are associated with disease activity, higher levels of acute-phase reactants and increase in TNF-a. 8 Molad et al, 9 in a prospective cohort study, reported that higher sTREM-1 levels are associated with an increase in titers of anti-CCP Abs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11 Different studies have observed an increase in plasma sTREM-1 levels in RA. [7][8][9] Choi et al observed that sTREM-1 levels are associated with disease activity, higher levels of acute-phase reactants and increase in TNF-a. 8 Molad et al, 9 in a prospective cohort study, reported that higher sTREM-1 levels are associated with an increase in titers of anti-CCP Abs.…”
Section: Discussionmentioning
confidence: 99%
“…Although, to the best of our knowledge, to date there is only a cohort study performed, with the aim of evaluating whether there is an association between serum sTREM-1 and clinical response in early RA treated with DMARDs. 9 Molad et al found that high sTREM-1 levels in RA predict a high Disease Activity Score assessing 28 joints (DAS)-28 after onset of therapy in patients who were DMARD naı¨ve. 9 However, a limitation of this study was the presence of a wide heterogeneity in therapeutic schemas, making interpretation of the study results difficult.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In rheumatoid arthritis (RA), TREM‐1 is over‐expressed in synovial tissues and its pharmacological inhibition limits destructive lesions of collagen‐induced arthritis . A few works have suggested that serum sTREM‐1 level may reflect RA disease activity, but they included small sample sizes of patients and the association between serum sTREM‐1 level and subsequent treatment response has not been addressed . Therefore, we aimed to investigate whether sTREM‐1 serum level is associated with disease activity and/or can predict response to biologic agents in RA patients.…”
Section: Characteristics Of 272 Rheumatoid Arthritis Patients Of the mentioning
confidence: 99%
“…3,4 A few works have suggested that serum sTREM-1 level may reflect RA disease activity, but they included small sample sizes of patients and the association between serum sTREM-1 level and subsequent treatment response has not been addressed. 5,6 Therefore, we aimed to investigate whether sTREM-1 serum level is associated with disease activity and/or can predict response to biologic agents in RA patients. This is an ancillary study of the Rotation or Change trial (NCT NCT01000441) in which 300 RA patients with an inadequate response to a first-line anti-tumor necrosis factor-alpha (anti-TNF-α) agent were randomized to switch to either a second anti-TNF-α or a non-anti-TNF0α higher in patients with Disease Activity Score of 28 joints using C-reactive protein (DAS28-CRP) >5.…”
mentioning
confidence: 99%